2013
DOI: 10.4028/www.scientific.net/amr.854.149
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in Antivirus Therapy

Abstract: The new mechanism of the virus activity inhibition is proposed. The idea is based on the nonspecific interaction between the viral particle and nanoparticles forming a stable bound state. The formation of the interaction potential between the virus and nanoparticles is caused by the presence of both linear and nonlinear polarizabilities, leading to the emergence of the attractive and repulsive parts of the potential, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The functionalized nanoparticles can affect the viruses due to chemical interactions between the molecules-functionalizers and molecules-receptors at the virus surface. The second direction is concerned with antiviral activity of 'pure' (non-functionalized) nanoparticles [3][4][5][6][7][8][9][10][11][12][13][14]. There are experimental results of antiviral action of Ag [3][4][5][6], Au [7,11], TiO 2 [8], CuCl 2 [9], CeO 2 [11][12][13][14], SiO 2 [10] nanoparticles against different viruses: influenza virus H3N2 and H1N1 [8,11], hepatitis B virus [3], herpes simplex virus [4,11], HIV-1 [5,6], dengue virus type-2 [9], Foot-and-Mouth disease virus [7], vesicular stomatitis virus [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The functionalized nanoparticles can affect the viruses due to chemical interactions between the molecules-functionalizers and molecules-receptors at the virus surface. The second direction is concerned with antiviral activity of 'pure' (non-functionalized) nanoparticles [3][4][5][6][7][8][9][10][11][12][13][14]. There are experimental results of antiviral action of Ag [3][4][5][6], Au [7,11], TiO 2 [8], CuCl 2 [9], CeO 2 [11][12][13][14], SiO 2 [10] nanoparticles against different viruses: influenza virus H3N2 and H1N1 [8,11], hepatitis B virus [3], herpes simplex virus [4,11], HIV-1 [5,6], dengue virus type-2 [9], Foot-and-Mouth disease virus [7], vesicular stomatitis virus [14].…”
Section: Introductionmentioning
confidence: 99%
“…The second direction is concerned with antiviral activity of 'pure' (non-functionalized) nanoparticles [3][4][5][6][7][8][9][10][11][12][13][14]. There are experimental results of antiviral action of Ag [3][4][5][6], Au [7,11], TiO 2 [8], CuCl 2 [9], CeO 2 [11][12][13][14], SiO 2 [10] nanoparticles against different viruses: influenza virus H3N2 and H1N1 [8,11], hepatitis B virus [3], herpes simplex virus [4,11], HIV-1 [5,6], dengue virus type-2 [9], Foot-and-Mouth disease virus [7], vesicular stomatitis virus [14]. Microscopic studies demonstrated that nanoparticles are adsorbed on the virus surface [6,7], which leads to local transformations of the surface, such as agglutination of glycoproteins [6,7], thus preventing virus penetration into the cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inhibitory mechanism of CeO 2 NPs can be obtained without requiring any surface modification by biomolecular covers. They also described the antiviral effect of AuNPs based on the above-mentioned process and explained the physical aspects of the mechanism of viral inhibition [134].…”
Section: Cerium Dioxide Nanoparticles (Ceo 2 Nps)mentioning
confidence: 99%
“…Several experimental reports of antiviral action of nanoparticles against different viruses like influenza virus H3N2 and H1N1 (Mazurkova et al 2010;Lysenko et al 2013), herpes simplex virus (Lysenko et al 2013;Hu et al 2014), hepatitis B virus (Lu et al 2008), HIV-1 (Elechiguerra et al 2005;Lara et al 2010), dengue virus type-2 (Sucipto et al 2017), Foot and Mouth disease virus (Rafiei et al 2016), vesicular stomatitis virus (Lokshyn et al 2014). Nanoparticles of silver (Hu et al 2014), gold (Sucipto et al 2017;Rafiei et al 2016), silicon Dioxide (Botequim et al 2012), copper (Sucipto et al 2017), titaniumdioxide (Mazurkova et al 2010), ceriumdioxide (Lokshyn et al 2014) are the few of the evaluated delivery system for their suppressive properties of viruses. Elechiguerra et al (2005) and Rafieiet al (2016) demonstrated the adsorption of nanoparticles on the surface of the virus, which leads to local surface transformations, such as glycoprotein agglutination, thus preventing virus penetration into the cell.…”
Section: Examples Of Biocompatible Systemsmentioning
confidence: 99%